2021
DOI: 10.1186/s12889-021-11190-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long working hours on health based on observations in China

Abstract: Background Health should be a key focus in considerations of long working hours. Little is known about for which groups of people working longer hours is more harmful to their health. Additionally, the definition of long working hours varies slightly due to country differences in working hours systems. Therefore, this study aims to explore the association between long working hours and the self-rated health (SRH) level, taking into account gender and educational differences. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…China's liberalization led to both a highly dynamic talent market and the subordination of women (Xiao & Asadullah, 2020). Executive working hours in China are high by Western standards, which has serious health implications, especially for women who carry both work and family responsibilities (Chu, 2021). In addition, the notion that men, and masculine characteristics, are inherently more competent than women in leadership roles is still held (Hu & Guan, 2021).…”
Section: China's Cultural and Political Backgroundmentioning
confidence: 99%
“…China's liberalization led to both a highly dynamic talent market and the subordination of women (Xiao & Asadullah, 2020). Executive working hours in China are high by Western standards, which has serious health implications, especially for women who carry both work and family responsibilities (Chu, 2021). In addition, the notion that men, and masculine characteristics, are inherently more competent than women in leadership roles is still held (Hu & Guan, 2021).…”
Section: China's Cultural and Political Backgroundmentioning
confidence: 99%
“…For example, studies of Korean workers indicated that precarious employment, such as temporary work, was associated with 1.31 times higher chance of poorer SRH for men and 1.34 times higher chance of poorer SRH for women [ 14 ]. The effects of long working hours on health is well studied in developed countries [ 15 ], although there is no strict definition of long working hours and the cut-offs for defining long working hours (e.g., ≥55 h/week) differ across studies [ 16 , 17 , 18 , 19 , 20 ]. Working long hours is associated with increased risk of chronic diseases and poor SRH [ 17 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of long working hours on health is well studied in developed countries [ 15 ], although there is no strict definition of long working hours and the cut-offs for defining long working hours (e.g., ≥55 h/week) differ across studies [ 16 , 17 , 18 , 19 , 20 ]. Working long hours is associated with increased risk of chronic diseases and poor SRH [ 17 , 19 , 20 , 21 , 22 , 23 ]. Two of the possible connections linking long working hours and poor health outcomes are physiological and behavioural mechanisms [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the era of rapid economic development, the quality of the workforce has attracted widespread attention, and in this regard, health is an important factor [1]. "According to various studies, there have been significant inequalities between men and women in terms of the incidence of psychological distress, and women suffer from psychological diseases to more than men" [2].…”
Section: Introductionmentioning
confidence: 99%
“…Among the reasons that cause women to experience burnout more, we can mention things such as long working hours. According to various reports, in recent years, the continuous increase in the working hours of employees had a direct impact on the health level of employees and has also harmed economic development and social stability [1]. "In addition, women do more additional work outside of their official roles, including managing household affairs and raising children.…”
Section: Introductionmentioning
confidence: 99%